INTERNET IN THE CONTEXT OF FINE ARTS EDUCATION - RÉCKA, Adriana (Trends in education, 2009)
The paper deals with the issue of the Internet application in the context of Fine Arts education. It brings closer its possibilities of utilization within the university preparation of Fine Arts teachers, including lectures and seminars with the impact put on web pages focused on presentation of culture-historical, architectonical and artistic works and educational programmes of galleries and museums.
Keywords: Fine Arts teacher education; Internet; Fine Arts history; educational programmes of galleries and museums.